Does less working time improve life satisfaction? Evidence from European Social Survey - Qinglong Shao (Health Economics Review, 2022)
Background: Worktime is one of the main drivers of life satisfaction, and a balanced distribution of working hours and leisure hours directly impacts feelings of well-being. Based on previous studies, we seek to confrm this relationship in the European context and explore other potential driving forces of life satisfaction. Health condition as the mediating variable is also examined. Methods: This article uses an ordered probit model to analyze the impact of working time on life satisfaction using data extracted from the most recent round (wave 10) of the European Social Survey (ESS). Hypotheses are proposed to test the impact of working time on life satisfaction, the mediating efect of health in the worktime-satisfaction nexus, and the efects of social inclusion, social trust, feelings of safety, and digitalization on life satisfaction. Results: The results reveal a negative and signifcant correlation between hours of work and life satisfaction, thus implying that a shorter working week can improve Europeans' life satisfaction. Health is found to be an important intermediate variable that plays an essential role in the dynamic through which working times infuence life satisfaction. Further, we fnd that those in the middle class prefer to work shorter hours to achieve a higher feeling of satisfaction and that high earners to a lesser extent, while low earners generally show no preference. Employees of private frms are more satisfed with shorter working hours, while satisfaction for those working in public institutions is not afected by changes in hours worked. Finally, we verify the robustness of our estimations by replacing life satisfaction with happiness. Conclusions: Working fewer hours contributes to higher life satisfaction in Europe, and health plays an essential mediating role in this relationship. Social inclusion, social trust, feelings of safety and digitalization all play a factor in improving life satisfaction. Compared to other job categories, private sector employees can achieve greater life satisfaction from reducing their total working time.
Keywords: 330; Life satisfaction; Working time; Ordered probit model; Health; Job category